PENGARUH KOMPETENSI DAN PRAKTEK AKUNTABILITAS TERHADAP PENCEGAHAN KECURANGAN (FRAUD) DALAM PENGELOLAAN DANA DESA DENGAN MORALITAS INDIVIDU SEBAGAI VARIABEL PEMODERASI - Kathleen Asyera Risakotta (JURNAL LENTERA AKUNTANSI, 2022)
This study aimed to examine the effect of competence and accountability practice on fraud prevention in the management of village funds with morality as a moderating variable. This study uses the questionnaire survey. Analysis of data using Moderated Regression Analysis (MRA). The results showed that competence and accountability practices significant effect on fraud prevention in the management of village funds. Individual Morality is able to moderate and competence on fraud prevention in the management of village funds. Individual Morality does not moderate accountability practice on fraud prevention in the management of village funds.Key words:      Competence, Accountability Practice, Individual Morality, Fraud Prevention, Moderated Regression Analysis